The antidepressant and anxiolytic effects of cannabinoids in chronic unpredictable stress: a preclinical systematic review and meta-analysis - Noa Reuveni; Cole A. Carlson; Sarah Schwartz; Diana Meter; Tyson S. Barrett; Sara M. Freeman (Translational Psychiatry, 2022)
Abstract Neuroscience research presents contradictory evidence in support of both the protective and destructive effects of cannabinoids in depression. Therefore, this systematic review and meta-analysis summarizes the existing preclinical literature on the effects of cannabinoid administration in the chronic unpredictable stress model of depression in order to evaluate the effects of cannabinoids and identify gaps in the literature. After protocol registration (PROSPERO #CRD42020219986), we systematically searched Scopus, Embase, Psychology & Behavioral Sciences Collection, APA PsychINFO, PubMed, CINAHL Complete, and ProQuest Dissertations & Theses Global from the earliest record of the databases, February 1964, to November 2020 for articles that met inclusion criteria (e.g., rodent subjects and administration of a cannabinoid. A total of 26 articles were included representing a sample size estimate of 1132 rodents with the majority of articles administering daily intraperitoneal injections during chronic unpredictable stress. These articles were evaluated using a modified SYRCLE’s risk-of-bias tool. For each continuous behavioral measure, the standardized mean difference was calculated between cannabinoid and vehicle groups in rodents subjected to chronic unpredictable stress. The effects of cannabinoids on depressive-like behavior was evaluated using a multilevel mixed-effects model with effect size weights nested within control groups. Cannabinoid administration moderately improved the pooled negative effects of chronic unpredictable stress on anhedonia, learned helplessness, novelty suppressed feeding, time in the anxiogenic context, and entries into the anxiogenic context. Although the interpretations are limited, these findings suggest that with further investigation, cannabinoids may be a viable long-term treatment for stress-related psychopathologies such as depression.